High Gain U-Slot antennas for RFID 915 MHz applications - Roshayati Mohamad (Universiti Malaysia Perlis, 2008)
This project describes a design of high gain U-slot antennas for RFID 915MHz applications. The frequency chosen is at 915 MHz (902 – 928 MHz) which is particular interest for RFID application. This work involves the design; performance optimization and fabrication of a printed antenna for RFID applications that can use several techniques as a folding, compacting and/or other miniaturization techniques. This antenna designs almost omnidirectional, low profile, small enough to be attached to the required object, robust and cheap for commercial purposes and convenience in use. In this receiver design, Agilent’s ADS software using momentum simulation is employed to analyze the entire structure. In the fabrication process, the proposed receiver element is printed on a FR4 substrate with a dielectric constant of 4.7, a thickness of 1.6 mm and a conductor loss of 0.019. Gain measurement will also be carried out to determine the radiation characteristics performance.